Towards universal Kangaroo Mother Care: recommendations and report from the First European conference and Seventh International Workshop on Kangaroo Mother Care. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ibe, O; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Ruiz Peláez, J G; et al. (Acta Paediatr, 2010)
UNLABELLED: The hallmark of Kangaroo Mother Care (KMC) is the kangaroo position: the infant is cared for skin-to-skin vertically between the mother's breasts and below her clothes, 24 h/day, with father/substitute(s) participating as KMC providers. Intermittent KMC (for short periods once or a few times per day, for a variable number of days) is commonly employed in high-tech neonatal intensive care units. These two modalities should be regarded as a progressive adaptation of the mother-infant dyad, ideally towards continuous KMC, starting gradually and progressively with intermittent KMC. The other components in KMC are exclusive breastfeeding (ideally) and early discharge in kangaroo position with strict follow-up. Current evidence allows the following general statements about KMC in affluent and low-income settings: KMC enhances bonding and attachment; reduces maternal postpartum depression symptoms; enhances infant physiologic stability and reduces pain, increases parental sensitivity to infant cues; contributes to the establishment and longer duration of breastfeeding and has positive effects on infant development and infant/parent interaction. Therefore, intrapartum and postnatal care in all types of settings should adhere to a paradigm of nonseparation of infants and their mothers/families. Preterm/low-birth-weight infants should be regarded as extero-gestational foetuses needing skin-to-skin contact to promote maturation. CONCLUSION: Kangaroo Mother Care should begin as soon as possible after birth, be applied as continuous skin-to-skin contact to the extent that this is possible and appropriate and continue for as long as appropriate.
Keywords: Congresses as Topic; Female; Global Health; Humans; Infant Care; Infant, Newborn; Male; Parent-Child Relations; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Skin